2020
DOI: 10.1021/acscatal.0c02475
|View full text |Cite
|
Sign up to set email alerts
|

Propyne Hydrogenation over a Pd/Cu(111) Single-Atom Alloy Studied using Ambient Pressure Infrared Spectroscopy

Abstract: The hydrogenation of propyne (C 3 H 4 ) to propene (C 3 H 6 ) using a Pd/Cu(111) single-atom alloy (SAA) has been studied using polarization-dependent reflection absorption infrared spectroscopy. This method allows for simultaneous monitoring of reactants and products in the gas phase and species adsorbed on the surface during the reaction. The results were compared with the hydrogenation of propyne using Pd-free Cu(111) as well as with previous studies on Pd/Cu SAA catalysts supported on alumina. Propene prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
(67 reference statements)
1
23
0
Order By: Relevance
“…This result demonstrates the suitability of this system for the isolation of a pure industrial propylene stream from propyne 41 , a task not accomplished by steam cracking but necessary for the production of polymer-grade propylene, which together with ethylene accounts for ~80% of global plastic demand 2 .…”
Section: Resultsmentioning
confidence: 84%
“…This result demonstrates the suitability of this system for the isolation of a pure industrial propylene stream from propyne 41 , a task not accomplished by steam cracking but necessary for the production of polymer-grade propylene, which together with ethylene accounts for ~80% of global plastic demand 2 .…”
Section: Resultsmentioning
confidence: 84%
“…In accord with the study of Chesters and McCash, 9 we assign the three major peaks at 2825, 2850, and 2883 cm −1 (enlarged spectra in the inset of Figure 1) to the first overtone of the asymmetric CH 3 deformation, the alkynic C−H stretch, and the symmetric CH 3 stretch, respectively. In a previous study, 15 we assigned the peak at 1358 cm −1 to a normal mode with mixed C 1 −C 2 stretch and δ(CH 3 ) character, as confirmed by the DFT calculations of Valcaŕcel et al 14 In the presence of 100 nTorr of propyne, the peak intensities shown in Figure 1 were constant up to 307.5 K but were lower at 310 and 320 K. At these higher temperatures, coupling reactions occur, leading to irreversible adsorption. The development of the peak at 2904 cm −1 was likely associated with a coupling product.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…Note that the IR intensity for the gas phase CO 2 can be well correlated with the amount of CO 2 under the experimental pressure. [ 21 ] In each reaction, 2 Torr gas mixture (CO: NO = 1 : 1) was filled, then risen to 623 K and held for 10 min, so the amounts of CO 2 can be compared.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, single‐atom catalysts (SAC) have attracted great attention in heterogeneous catalysis. It had been shown that single‐atom catalysts exhibited a much better catalytic performance than traditional nanoparticle catalysts in many reactions, such as CO oxidation, [ 16‐19 ] selective hydrogenation/dehydrogenation [ 20‐21 ] and water‐gas shift reaction (WGS). [ 22‐24 ] However, clusters and nanoparticles exhibited a higher catalytic activity than single‐atom for some reactions.…”
Section: Background and Originality Contentmentioning
confidence: 99%